How to Choose a Binarization Algorithm for a Document Image? - Lins, Rafael Dueire; Chaves, Gustavo P.; Vieira, Thaylor; Barboza, Ricardo Da Silva (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI), 2024)
This document is a tutorial on how to choose a binarization algorithm for a document image, considering different analysis criterias. This tutorial focuses on some main challenges one can face when dealing with binarization algorithms.